Characterization and polarization DRT analysis of a stable and highly active proton-conducting cathode. Issue 12 (15th August 2018) - Cai, Wei; Guo, Yangyang; Zhang, Teng; Guo, Tianming; Chen, Hui; Lin, Bin; Ou, Xuemei; Ling, Yihan
Abstract: The development of high active cathode materials owning low activation energy (Ea) is the most critical core for protonic solid oxide fuel cells (P-SOFCs). Considering this challenge, we herein develop Ba0.9 La0.1 Co0.4 Fe0.4 Zr0.1 Y0.1 O3-δ -BaZr0.1 Ce0.7 Y0.2 O3-δ (BLCFZY-BZCY) composite as a new proton conducting cathode for P-SOFCs. Anode supported single cells with BLCFZY-BZCY cathode show remarkable performance and low electrode Ea of 83.41 kJ mol −1 . High power densities of 752 and 206 mW cm −2 are achieved at 700 and 500 °C, respectively, while corresponding electrode interfacial polarization resistances (Rp) are 0.08 and 1.2 Ω cm 2 . Interestingly, the electrode polarization processes with a high resolution based on the impedance spectra data were further analyzed using the distribution function of relaxation time (DRT). Three same polarization peaks (P1, P2, P3) meaning three rate-limiting steps are existed in the DRT curves with different temperature, where P3 resulting from the cathode-electrolyte interfacial resistance with oxygen species involved reactions is the dominant rate-limiting step with a proportion of over 49.6% while the anode-electrolyte interfacial resistance corresponding to P1 has almost no increase, from 0.03 Ωcm 2 to 0.09 Ωcm 2 . The experimental results demonstrate BLCFZY-BZCY composite can be a promising proton conducting cathode for P-SOFCs. Highlights: Electronic barrier layer can cut off the internal shorting of ceria-based SOFCs. Effect of the electronic barrier layer was simulated by a mathematic model. Ceria-based SOFCs show good carbon-tolerance in wet methane. Carbon deposition boundary was predicted considering anodic hygroscopicity.